Depiction of Exclusive Breastfeeding in Tribunnews and Republika.co.id Using Topic Modeling - Rahma Mesi Shabrina (Universitas Medan Area, 2023)
Breast milk is the best food for babies aged 0-6 months and is recommended to be continued until the baby is 2 years old. Exclusive breastfeeding can prevent stunting in toddlers. The prevalence of stunting in Indonesia in 2021 is still higher than the WHO target. The media can become friends in promoting the Exclusive Breastfeeding program through their coverage. This study uses the topic modeling method to see how the news coverage of exclusive breastfeeding by Tribunnews and Republika.co.id during 1 January 2021-15 November 2022. This research found five of the seven topics are same in these two media; world breastfeeding week, Mothers positive for Covid-19 can still give breast milk, nutrition of breast milk, Covid-19 vaccination for breastfeeding mothers and breast milk can prevent stunting. Different topics include health services for breastfeeding mothers and babies as well as health problems for breastfeeding mothers on Tribunnews. While Republika.co.id covers religion and breastfeeding as well as support for breastfeeding mothers. The tone of news regarding exclusive breastfeeding in both media is relatively positive. However, the coverage on exclusive breastfeeding is still lacking in quantity both on Tribunnews and Republika.co.id.